Education on Making Local Fish Spawning Stimulants for the Pokdakan Karya Maju in Karya Tani Village: Edukasi Pembuatan Bahan Perangsang Pemijahan Ikan Lokal Untuk Pokdakan Karya Maju Desa Karya Tani - Akhmad Murjani; Siswanto Siswanto; Untung Bijaksana; Indira Fitriliyani; Muhammad Adriani; Ermalia Herawati (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Pokdakan Karya Maju is one of the fish farming groups located in Karya Tani Village, Barambai District, Barito Kuala Regency. The problem faced by Pokdakan is that they have not been able to produce their own seeds. This is because the spawning process requires special and specific skills and knowledge. Pokdakan must always buy seeds from the Seedling Center for the sustainability of their business. This is certainly risky for the sustainability of the business if they fail to get fish seeds. This community service activity (PkM) aims to educate Pokdakan about making local fish spawning materials from the pituitary gland. The approach method used is socialization and demonstration, question and answer which is then carried out to evaluate the knowledge and skills of the target audience with a t-test. The results of the pretest and posttest evaluations showed an increase in the knowledge and skills of the target audience from an average of 19% to 80.57%. The results of the t-test showed that thit (1.982) > ttab (1.734) which means that the change was significant.